2017
DOI: 10.1080/01616412.2016.1275455
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing carpal tunnel syndrome with Doppler ultrasonography: a comparison of ultrasonographic measurements and electrophysiological severity

Abstract: Our study shows that Doppler ultrasonography results strongly correlate with CTS severity. Hence, this is a useful method for diagnosing CTS and estimating its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 21 publications
1
64
1
Order By: Relevance
“…That there is a hyperemic response of injured nerves has also been confirmed independently by morphometric analysis, identifying endoneurial microvascular dilatation early after injury . More recently, hyperemia has been detected in human median nerves entrapped at the carpal tunnel …”
Section: Nbf and Nerve Injurymentioning
confidence: 72%
See 1 more Smart Citation
“…That there is a hyperemic response of injured nerves has also been confirmed independently by morphometric analysis, identifying endoneurial microvascular dilatation early after injury . More recently, hyperemia has been detected in human median nerves entrapped at the carpal tunnel …”
Section: Nbf and Nerve Injurymentioning
confidence: 72%
“…Later advanced cases had declines. In contrast, Kutlar et al identified a significant correlation between CTS severity and median nerve hypervascularization. Joy et al used apparent rises in median NBF for the diagnosis of CTS and noted a linear relationship between flow values they obtained with other measures of CTS.…”
Section: Human Studies Of Nbfmentioning
confidence: 86%
“…Studies on the diagnostic accuracy of US in detecting CTS have centered mainly on the CSA of the median nerve, measured either at the CTI or CTO. There are studies that have examined different US parameters but did not conduct a regression analysis to determine whether combined measurements are more diagnostically discriminatory . Using stepwise multiple logistic regression models, this study demonstrated that the wrist‐forearm difference coupled with evidence of hypervascularity at the CTO were predictive parameters for CTS with high sensitivity (98.1%).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, venous outflow is blocked in early stages of CTS, which may result in blood accumulation and increased pressure in the area of entrapment. This will reduce the signal detected by Doppler US; however, there may be compensatory dilatation of peripheral veins, resulting in a net signal increase . Studies by Kutlar et al and Ooi et al showed that hypervascularity with a cutoff of 0.0020 cm 2 and the presence of at least a single neovessel of greater than 1 mm in length in the sagittal plane had sensitivity of 93.4% and 69%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation